Estrategia de sensibilización para evitar la deserción escolar de niñas y niños de nivel primario a través del proyecto "Pienso, opino y participo" de Global Humanitaria Perú - Castro Ayerbe, Mercedes (2021)
The arrival of COVID 19 in our country has caused different impacts in different areas. In terms of education, the lack of connectivity has posed different challenges for lowincome families, especially in rural areas, and many parents are prioritizing the acquisition of economic resources over their children's right to education, ignoring future consequences. On the other hand, teachers have been doing an arduous task for their students to continue with their daily learning, many times without success, which causes demotivation on both sides. Faced with this scenario, the Global Humanitaria Peru association has been working on a project called: "I think, I think and I participate" which seeks to contribute to improving access to the right to education for girls and boys in primary schools in the Puno region. In this work, awareness strategies are carried out for the three main educational actors of the same level: teachers, parents, girls and boys, to influence access to the right to education and improve joint work in order to avoid the school dropout of girls and boys, which will contribute to achieving the objectives of said organization.